2005
DOI: 10.1074/jbc.m502211200
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Vpr Protein Activates Activator Protein-1, c-Jun N-terminal Kinase, and NF-κB and Stimulates HIV-1 Transcription in Promonocytic Cells and Primary Macrophages

Abstract: The human immunodeficiency virus (HIV)Vpr

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
75
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(78 citation statements)
references
References 85 publications
2
75
1
Order By: Relevance
“…This event leads to permeabilization of the outer mitochondrial membrane with consequent release of apoptosis-inducing factor and cytochrome c (9,19). Cytochrome c interacts with Apaf-1 and procaspase 9 to create an apoptosome, the caspase activation complex that causes activation of other caspases resulting in apoptosis (8,9,19 (10,48), this is the first report describing a novel pathway involving JNK activation in Vpr-induced apoptosis. The JNK group of MAPKs is encoded by three genes: jnk1 and jnk2 genes, which are ubiquitously expressed, and the jnk3 gene expressed primarily in the heart, testis, and brain (49).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…This event leads to permeabilization of the outer mitochondrial membrane with consequent release of apoptosis-inducing factor and cytochrome c (9,19). Cytochrome c interacts with Apaf-1 and procaspase 9 to create an apoptosome, the caspase activation complex that causes activation of other caspases resulting in apoptosis (8,9,19 (10,48), this is the first report describing a novel pathway involving JNK activation in Vpr-induced apoptosis. The JNK group of MAPKs is encoded by three genes: jnk1 and jnk2 genes, which are ubiquitously expressed, and the jnk3 gene expressed primarily in the heart, testis, and brain (49).…”
Section: Discussionmentioning
confidence: 94%
“…Pretreatment of cells with JNK inhibitors SP60025 and DXM or transfection with JNKspecific siRNAs significantly inhibited Vpr-induced apoptosis. Although MAPKs have been reported to regulate HIV replication in T cells and latently infected cells (10,48), this is the first report describing a novel pathway involving JNK activation in Vpr-induced apoptosis. The JNK group of MAPKs is encoded by three genes: jnk1 and jnk2 genes, which are ubiquitously expressed, and the jnk3 gene expressed primarily in the heart, testis, and brain (49).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, NF-κB is increasingly considered as a target for anti-cancer drug treatment (23)(24)(25)(26)(27). Many studies have demonstrated that Vpr was able to block NF-κB activation (37,38), whereas others reported that Vpr may also activate NF-κB and protect cells from apoptosis (18,39). However, in the current study, we further confirmed that Ad-Vpr was able to inhibit NF-κB activation in a time-dependent manner through the upregulation of IκBα in the cytoplasm, and inhibition of nuclear translocation of p65 and DNA-binding activity of p65.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the Vpr protein appears to preferentially inhibit the growth of rapidly dividing tumor cells, but does not affect the normal cells regardless of changes in p53 expression (7)(8)(9)15). Most importantly, the Vpr protein can easily penetrate the cell membrane without the help of a receptor or carrier (16)(17)(18) …”
Section: Introductionmentioning
confidence: 99%